Pengaruh Product Differentiation, Brand Image Dan Harga Terhadap Keputusan Pembelian Di KFC Kota Probolinggo - Maulidi, Achmad; Hudzafidah, Khusnik; ., Junaidi (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
This research aims to determine the influence of product differentiation, brand image and price on purchasing decisions. Quantitative research with causal associative relationships is the type of research used. product differentiation (X1), brand image (X2) and price (X3) are independent variables. Meanwhile, the purchasing decision (Y) is the dependent variable used in this research. The sample in this research was 100 customers from a total population of 160 customers. The sample used in this research was incidental sampling. The temporary conjecture test (Hypothesis) can be concluded, namely that the product differentiation variable obtained the value tcount > ttable (2.393 > 1.660) indicating that product differentiation has a significant effect on purchasing decisions, the brand image variable obtained the value tcount > ttable (2.001 > 1.660) indicating that brand image has a significant effect on purchasing decisions and the price variable obtained by the value tcount > ttable (2.948 > 1.660) shows that price has a significant effect on purchasing decisions.